2015
DOI: 10.1016/j.jor.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of multiple quality characteristics in bone drilling using grey relational analysis

Abstract: Bone drillingGrey relational analysis (GRA) Analysis of variance (ANOVA) a b s t r a c t Purpose: Drilling of bone is common during bone fracture treatment to fix the fractured parts with screws wires or plates. Minimally invasive drilling of the bone has a great demand as it helps in better fixation and quick healing of the broken bones. The purpose of the present investigation is to determine the optimum cutting condition for the minimization of the temperature, force and surface roughness simultaneously dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Sawbones were preferred to real human cancellous bone to avoid variability. To perform this study, a statistical design of experiments (SDOE) was used to optimize multiple performance characteristics on K-wires fixation (Pandey and Panda 2015;Singh et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sawbones were preferred to real human cancellous bone to avoid variability. To perform this study, a statistical design of experiments (SDOE) was used to optimize multiple performance characteristics on K-wires fixation (Pandey and Panda 2015;Singh et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the temperature exposure time, the probability of necrosis increases, and when the temperature is as high as 70 C, thermal necrosis occurs immediately [5]. Also, excessive thrust force of drilling causes micro cracks in the bone, which extends the bone recovery time [6]. In other words, thrust force is directly related to temperature increase in cortical bone during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Augustin et al [23] studying pig bone, found that a higher tool diameter increases the contact between the bone and drill, and causes high friction between the drill and bone and consequently increases the temperature of the process. Pandey and Panda [6,24,25] used Taguchi approach and computed the optimal process force and temperature as a function of feed rate and rotational speed, but did not consider the interaction between the parameters. Furthermore, Boyadjiev et al [26,27] designed an experimental setup and identified that automatic bone drilling can solve the high-temperature problem which arises during manual drilling.…”
Section: Introductionmentioning
confidence: 99%
“…In orthopaedics surgery, bone drilling is widely known to create hole for insertion of screw [1]. Before the insertion of screw, drilling then tapping are conducted [2].…”
Section: Introductionmentioning
confidence: 99%